How Did Italians Communicate When There Was No Italian? Italo-Romance Intercomprehension in the Late Middle Ages. (2nd January 2020) - Carlucci, Alessandro
ABSTRACT: Historians (including historians of oral and written culture, and to some extent also literary historians) have long been aware of the role of Latin as a potential barrier to intelligibility, but they have very rarely considered the possibility that Italy's vernacular varieties could equally impede communication. Linguists, on the other hand, are for the most part convinced that medieval speakers were trapped in a myriad of mutually unintelligible vernaculars. In this article, these conflicting views are tested on a range of late medieval sources, which reveal how speakers perceived the lexicon as the structural level creating the main problems of intelligibility. In some cases, phonological and morphological differences were also perceived as sources of misunderstanding and as potential barriers to communication. On the whole, however, these barriers do not seem to have been as insurmountable as the traditional views of most linguists would lead us to expect.